KAJIAN KETERPADUAN PENGELOLAAN DAERAH ALIRAN SUNGAI (DAS) GARANG PROVINSI JAWA TENGAH - Fatahilah, Muhammad (Jurnal Geografi, 2013)
Garang watershed is one of critical watershed with first priority treatment. Thedamage of Garang watershed have caused environment problem in SemarangCity become more complex. Natural limit of Garang watershed which lay onbetween Semarang Regency, Kendal Regency and Semarang City, need integrityin itâs management. This research aimed to assess the integrity level of Garangwatershed management and formulate strategy to improve it. This is descriptiveresearch with qualitative and quantitative approach which focused on integritymanagement function of Garang watershed. The aspects which assessed wereplanning integrity, organization, action and control. While strategy analysisusing AHP. The result showed that the integrity level of Garang watershedmanagement was still low, so it need a strategy to improve it. The prioritystrategy which can be used are arrangement of integrity planning management,organizing watershed limit with administrative area, and clearly separation offunction from each stakeholder in Garang watershed management.